\(x^3-2x-4\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

28 tháng 6 2018

\(x^3-2x-4=x^3-4x+2x-4=x\left(x-2\right)\left(x+2\right)+2\left(x-2\right)=\left(x-2\right)\left(x^2+2x+2\right)\)

6 tháng 10 2018

      \(x^6-x^4+2x^3+2x^2\)

\(=x^2\left(x^4-x^2+2x+2\right)\)

\(=x^2\left[x^4-2x^3+x^2+2x^3-4x^2+2x+2x^2-4x+2\right]\)

\(=x^2\left[x^2\left(x^2-2x+1\right)+2x\left(x^2-2x+1\right)+2\left(x^2-2x+1\right)\right]\)

\(=x^2\left(x^2-2x+1\right)\left(x^2+2x+2\right)\)

\(=x^2\left(x-1\right)^2\left(x^2+2x+2\right)\)

25 tháng 10 2017

Ta có : \(x^4+x^3+2x^2+x+1\)

\(=x^4+x^3+x^2+x^2+x+1\)

\(=x^2\left(x^2+x+1\right)+\left(x^2+x+1\right)\)

\(=\left(x^2+x+1\right)\left(x^2+1\right)\)

26 tháng 11 2016

x^4-x^3-x^2+2x-2

=(x^4-x^3)-(x^2-2x+2)

=x^3(x-1)-(x-1)^2

=(x^3-x-1)*(x-1)

26 tháng 11 2016

X4-X3-X2+2X -2= (X4-X3-X2)+(2X-2) = X2(X2-1-X)+2(X-1)  = X2((X-1)(X+1)-X) +2(X-1) = X3+X2-X3(X-1)+2(X-1) = X2(X-1)-X3(X-1)+2(X-1)

=(X2-X3+2)(X-1)

6 tháng 4 2017

\(x^4+2x^3-6x-9\)  

\(=x^4-9+2x^3-6x\) 

\(=\left(x^2-3\right)\left(x^2+3\right)+2x\left(x^2-3\right)\) 

\(\left(x^2-3\right)\left(x^2+3+2x\right)\) 

13 tháng 9 2020

x4 + 2x3 + x2 - y2

= ( x4 + 2x3 + x2 ) - y2

= [ ( x2 )2 + 2.x2.x + x2 ] - y2

= ( x2 + x )2 - y2

= ( x2 + x - y )( x2 + x + y )

13 tháng 9 2020

\(=x^2\left(x^2+2x+1\right)-y^2\)

\(=x^2\left(x+1\right)^2-y^2\)

\(=x^2\left(x+1-y\right)\left(x+1+y\right)\)

3 tháng 7 2019

\(x^8+3x^4+4\)

\(=\left(x^8-x^6+2x^4\right)+\left(x^6-x^4+2x^2\right)+\left(2x^4-2x^2+4\right)\)

\(=x^4\left(x^4-x^2+2\right)+x^2\left(x^4-x^2+2\right)+2\left(x^4-x^2+2\right)\)

\(=\left(x^4+x^2+2\right)\left(x^4-x^2+2\right)\)

3 tháng 7 2019

\(4x^4+4x^3+5x^2+2x+1\)

\(=\left(4x^4+2x^3+2x^2\right)+\left(2x^3+x^2+x\right)+\left(2x^2+x+1\right)\)

\(=2x^2\left(2x^2+x+1\right)+x\left(2x^2+x+1\right)+\left(2x^2+x+1\right)\)

\(=\left(2x^2+x+1\right)^2\)

29 tháng 1 2019

\(x^4+2x^3+3x^2+2x+1.\)

\(=x^4+x^3+x^3+x^2+x^2+x^2+x+x+1\)
\(=x^4+x^3+x^2+x^3+x^2+x+x^2+x+1\)

\(=x^2\left(x^2+x+1\right)+x\left(x^2+x+1\right)+\left(x^2+x+1\right)\)

\(=x^2\left(x+1\right)^2+x\left(x+1\right)^2+\left(x+1\right)^2\)

\(=\left(x+1\right)^2\left(x^2+x+1\right)\)

\(=\left(x+1\right)^2\left(x+1\right)^2\)

\(=\left(x+1\right)^4\)

29 tháng 1 2019

@wi

\(x^2+x+1=\left(x+1\right)^2???\)

\(x^2+2x+1=\left(x+1\right)^2\)chứ